Elucidating the dynamics of polymer transport through nanopores using asymmetric salt concentrations - Charron, Martin; Philipp, Lucas; He, Liqun; Tabard-Cossa, Vincent (Nano research, 2022)
While notable progress has been made in recent years both experimentally and theoretically in understanding the highly complex dynamics of polymer capture and transport through nanopores, there remains significant disagreement between experimental observation and theoretical prediction that needs to be resolved. Asymmetric salt concentrations, where the concentrations of ions on each side of the membrane are different, can be used to enhance capture rates and prolong translocation times of electrophoretically driven polymers translocating through a nanopore from the low salt concentration reservoir, which are both attractive features for single-molecule analysis. However, since asymmetric salt concentrations affect the electrophoretic pull inside and outside the pore differently, it also offers a useful control parameter to elucidate the otherwise inseparable physics of the capture and translocation process. In this work, we attempt to paint a complete picture of the dynamics of polymer capture and translocation in both symmetric and asymmetric salt concentration conditions by reporting the dependence of multiple translocation metrics on voltage, polymer length, and salt concentration gradient. Using asymmetric salt concentration conditions, we experimentally observe the predictions of tension propagation theory, and infer the significant impact of the electric field outside the pore in capturing polymers and in altering polymer conformations prior to translocation.